Kinerja return sektor transportasi dan logistik papan utama menjelang Idul Fitri - Katarina Ersyn Marysan; Kesya Ourisa Sembiring (Yayasan Widyantara Nawasena Raharja, 2023)
The transportation and logistics sector faced complex problems during the COVID-19 pandemic but had opportunities when the PPKM was repealed, especially regarding religious holidays. The purpose of this study is to examine the return performance of the transportation and logistics sector in the context of religious holidays. This study finds that a better rate of return occurs in the period leading up to Idul Fitri, although it is not significantly different from the non-holiday period. In addition, this study also finds that the risk-return performance of this sector is quite optimal in the period leading up to the Idul Fitri holiday.